Effect of oxygen flow rate on the ultraviolet sensing properties of zinc oxide nanocolumn arrays grown by radio frequency magnetron sputtering. Issue 3 (15th February 2016) - Mamat, M.H.; Malek, M.F.; Hafizah, N.N.; Asiah, M.N.; Suriani, A.B.; Mohamed, A.; Nafarizal, N.; Ahmad, M.K.; Rusop, M.
Abstract: Highly transparent metal–semiconductor–metal ultraviolet (UV) photoconductive sensors were fabricated using thin (less than 100 nm in thickness), dense, small-diameter ZnO nanocolumn arrays prepared via low-power, catalyst-free radio frequency (RF) magnetron sputtering at different oxygen flow rates ranging from 0 to 25 sccm. The FESEM images revealed the average nanocolumn diameter decreased with increasing oxygen flow rate. The transmittance spectra show that with the introduction of oxygen, the transmittance of the nanocolumn arrays in the visible region improves relative to that of a film prepared in the absence of oxygen with values greater than 95%. The UV responsivity and sensitivity were significantly improved for sputtered ZnO nanocolumn arrays prepared at oxygen flow rates up to 10 sccm, with the highest values of 9.70 mA/W and 2.20×10 4 . Furthermore, the responsivity and sensitivity decreased at oxygen flow rates greater than 10 sccm, which can be attributed to the increased electrical resistance of the nanocolumn arrays. Our findings indicate that a high-performance UV photoconductive sensor can be realised using very thin sputtered ZnO nanocolumn arrays and that such a sensor would exhibit high sensitivity.